Effects of DC Magnetic Fields on Magnetoliposomes - Nuñez-Magos, L.; Lira-Escobedo, J.; Rodríguez-López, R.; Muñoz-Navia, M.; Castillo-Rivera, F.; Viveros-Méndez, P. X.; Araujo, E.; Encinas, A.; Saucedo-Anaya, S. A.; Aranda-Espinoza, S. (Frontiers in Molecular Biosciences, 2021)
The potential use of Magnetic Nanoparticles (MNP) in biomedicine as drug-delivery, imagenology, hyperthermia, and biosensors, has been studied in different laboratories. One of the challenges on MNP elaboration for biological applications is biocompatibility, stabilization in physiological conditions, and surface coating. Magnetoliposomes (MLS), a lipid bilayer of phospholipids encapsulating MNPs, is a system used to reduce toxicity. Encapsulated MNP can be used as a potential drug and gene delivery system, and in the presence of magnetic fields, MLS can be accumulated in a target tissue by a strong gradient magnetic field. Here we present a study of the effects of DC magnetic fields on encapsulated MNP inside liposomes. Despite the widespread applications in biotechnology, environmental, biomedical, and material science, it remains unclear the effects of magnetic fields on magnetoliposomes. We use a modified co-precipitation method to synthesize Superparamagnetic Nanoparticles (SNP) in aqueous solutions. The SNP are encapsulated inside phospholipid liposomes to study the interaction between phospholipids and SNPs. Material characterization of SNP reveals round-shape nanoparticles with an average size of 12 nm and mainly magnetite. Magnetoliposomes (MLS), was prepared by rehydration method. After formation, we found two types of MLS: The first MLS that is tense with SNP encapsulated, and the second type of vesicles is a floppy vesicle that does not show the presence of SNP. To study the response of the MLS to an applied DC magnetic field, we used a homemade chamber. Digitalized images show encapsulated SNP assemble in chain formation when a DC magnetic field is applied. When the magnetic field is switched off, completely disperse SNP. Floppy MLS deform along the direction of the external applied magnetic field. Solving the relevant magnetostatic equations, we present a theoretical model to explain the MLS deformations by analyzing the forces exerted by the magnetic field over the surface of the spheroidal liposome. Tangential magnetic forces acting on the MLS surface result in a press force deforming MLS. The type of deformations will depend on the magnetic properties of the mediums inside and outside the MLS. The model predicts a coexistence region of oblate-prolate deformations in the zone where $χ$=1.